Design of an Inclusive Digital Platform for Training and Distribution of Human Resources in Improving Accessibility and Opportunities for Persons with Disabilities - Risky Sanjaya; Dedi Irawan (Golden Ratio of Data in Summary, 2024)
This study addresses the challenges faced by individuals with disabilities in accessing employment opportunities in Indonesia, focusing on the creation of a digital platform that enhances their employability. The research was conducted at Sentra Budi Perkasa in Palembang City, a center that already utilizes an online training registration system but struggles with effective distribution of resources to its trainees. The primary objective was to develop a web-based platform that facilitates registration and improves access to job vacancies for persons with disabilities capable of using electronic devices. Through a combination of observations, interviews, and literature reviews, this study explored the needs and barriers encountered by this demographic, particularly those affected by conditions such as amputation, stroke, and congenital disorders. The Rapid Application Development (RAD) methodology was employed, ensuring a swift development process and involving users actively to reduce errors and enhance system relevance. The resulting platform not only simplifies the process of finding training and job opportunities for persons with disabilities but also serves as a model for similar initiatives aiming to integrate disabled individuals into the workforce more effectively. This study contributes to the field by providing a practical solution to a significant societal issue and outlining a framework for future enhancements in digital accessibility for disabled populations.